A sodium ferric sulfate positive electrode material and a dry preparation process thereof by grading grinding

CN122930860APending Publication Date: 2026-10-16CHAOWEI POWER GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610738336.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0012]本发明的主要目的在于提供一种硫酸铁钠正极材料及其分级干法研磨工艺,以解决现有单一干法研磨工艺中,振动球磨机(或卧式球磨机)研磨时间长、球料比高、设备易损、产线产量低,以及单一干法砂磨机碳源上浮、混合不均、研磨效果差的问题

Benefits of technology

[0034] (2) Balance between efficiency and quality: By employing a two-stage division of labor, the extreme conditions that a single piece of equipment must endure to achieve the same effect are avoided. The vibratory mill only needs to perform "coarse grinding" rather than "fine grinding," thus significantly shortening the grinding time (2-6 hours), reducing the ball-to-material ratio (5:1-15:1), and significantly reducing equipment wear and energy consumption. The dry sand mill, because the carbon source has already been premixed in the feed, avoids the problem of carbon source floating, and only 1-3 cycles are needed to achieve the ideal nano-scale effect, greatly improving grinding efficiency. This invention adopts a two-stage grinding dry preparation process, which can significantly increase the output per unit time of the production line and effectively reduce the overall material cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930860A_ABST
    Figure CN122930860A_ABST
Patent Text Reader

Abstract

The application relates to a sodium ferric sulfate positive electrode material and a dry-process preparation process thereof. The preparation process comprises the following steps: firstly, adding an iron source, a sodium source and a carbon source into a ball mill according to a proportion to perform primary coarse grinding, realizing pre-coating of the carbon source through high-impact force and mechanical force chemical action of large-size media; then, moving the coarse grinding material to a dry-process sand mill to perform secondary fine grinding, performing fine grinding through high-shear force of small-size media, reducing the particle size to a submicron level, and further homogenizing the carbon coating layer; finally, obtaining a sodium ferric sulfate positive electrode material finished product through processes such as sintering, crushing and grading, and magnetic removal. The application can greatly shorten the grinding time, reduce the ball-to-material ratio and equipment wear, effectively solve the carbon source floating problem, significantly improve the yield, reduce the material cost, and the prepared sodium ferric sulfate positive electrode material has a specific capacity of 90-95 mAh / g, good electrochemical performance and cycle stability, and is easy to scale up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a sodium iron sulfate cathode material and its graded grinding dry preparation process. Background Technology

[0002] With the global energy structure transformation and the rapid development of the electric vehicle industry, sodium-ion batteries, due to their abundant resources, low cost, and high safety, have shown broad application prospects in large-scale energy storage and low-speed electric vehicles. The cathode material is a key factor determining the energy density, cycle life, and cost of sodium-ion batteries. Among many cathode material systems, sodium iron sulfate (Na₂SO₄) is a popular choice. 2+2X Fe 2-X (SO4)3) polyanionic cathode materials have become a research hotspot due to their unique crystal structure and physicochemical properties. These materials have the following advantages: (1) high theoretical specific capacity (approximately 100-120 mAh / g), and actual reversible capacity reaching 90-110 mAh / g; (2) a relatively high operating voltage platform (approximately 3.6-3.8 V vs. Na). + / Na), high energy density; (3) polyanionic framework (SO4 3- (4) It has strong covalent bonding and excellent thermal stability; (5) It has abundant raw material sources, with iron and sodium reserves far exceeding those of lithium and cobalt, and most of the raw materials come from industrial by-products, resulting in significant cost advantages.

[0003] However, the electrochemical performance of sodium ferric sulfate cathode materials is highly dependent on their microstructure, particularly the size of the active particles and the uniformity of the conductive carbon network. This is because sodium ferric sulfate has a low intrinsic electronic conductivity (<10). -8 The rate performance and cycle stability of materials with a speed of S / cm must be improved through nano-sizing and compositing with conductive carbon materials. Therefore, in large-scale production, achieving efficient mixing and fine grinding of iron, sodium, and carbon sources is a key technical aspect that determines the final performance of the material.

[0004] Currently, the grinding and mixing processes for sodium ferric sulfate precursors are mainly divided into two categories: wet processes and dry processes. I. Wet process route for preparing sodium ferric sulfate cathode material Wet grinding processes typically employ sand mills as the core grinding equipment, conducted in water or organic solvents (such as ethanol, N-methylpyrrolidone, etc.). This process can grind materials to submicron or even nanometer scales (D50 ≤ 1 μm), and the carbon source can be fully wetted and dispersed in the liquid medium, thereby achieving highly uniform mixing with the active material. Currently, the wet route in the preparation of sodium ferric sulfate precursor mainly forms the following two typical processes: Route 1 (Step-by-Step Method): Ferrous sulfate, sodium sulfate, and deionized water are added to a sand mill in a specific ratio and mixed at high speed to form a homogeneous slurry. The resulting slurry is then spray-dried to quickly remove moisture, yielding a sodium ferric sulfate precursor powder with good sphericity and uniform composition. Subsequently, the precursor powder is subjected to high-temperature drying (to further remove residual moisture and structural water), and then added together with a carbon source (such as carbon nanotubes (CNTs), graphene, conductive carbon black, etc.) to a vibratory ball mill or other ball milling equipment for solid-phase carbon coating, ultimately obtaining a carbon-composite sodium ferric sulfate precursor.

[0005] Route 2 (One-Step Method): Ferrous sulfate, sodium sulfate, a carbon source (such as carbon nanotubes (CNTs), graphene, conductive carbon black, etc.), a dispersant, and deionized water are added to a sand mill in one step. Wet grinding is used to fully mix and nano-size the components in the liquid phase, forming a uniform and stable composite slurry. Subsequently, the slurry is directly spray-dried, achieving in-situ coating of the sodium ferric sulfate particles with the carbon source during the drying process, resulting in a carbon-composite sodium ferric sulfate precursor powder in one step. This route eliminates the need for a separate subsequent carbon coating process, simplifying the process flow.

[0006] While both wet processing methods described above can achieve good nano-sizing and carbon dispersion effects, they both share the following common problems: 1. Complex process and high energy consumption: The slurry has a low solid content and requires a large amount of solvent as a medium. It then undergoes multiple drying processes (spray drying, vacuum drying), resulting in extremely high energy consumption for the product.

[0007] 2. It requires an additional solvent recovery process, which puts significant pressure on environmental protection, requires substantial equipment investment, and occupies a large area.

[0008] 3. Moisture sensitivity: Sodium-ion battery materials are extremely sensitive to moisture. If the moisture introduced by wet milling is not completely removed, it may cause side reactions during the subsequent sintering process, affecting the crystal structure and electrochemical performance of the material.

[0009] 4. Cost disadvantages: Solvent consumption, drying energy consumption, and environmental treatment costs make the overall cost of the wet process much higher than that of the dry process, thus weakening the cost advantage of sodium batteries.

[0010] II. Process Route for Preparing Sodium Ferric Sulfate Cathode Material by Dry Grinding with Single Equipment Dry grinding has become an important research direction for the industrialization of sodium ferric sulfate due to its advantages such as short process, no need for solvent recovery, simple equipment, and low cost. However, existing single dry grinding equipment each has its own insurmountable shortcomings: Disadvantages of single-vibration ball mill (or horizontal ball mill, etc.) processes: Vibratory ball mills and horizontal ball mills utilize the impact and shearing action of grinding media (zirconia balls, alumina balls, etc.) to grind and pulverize a mixture of ferrous sulfate monohydrate (or anhydrous ferrous sulfate), anhydrous sodium sulfate, and carbon sources (such as carbon nanotubes CNTs, conductive carbon black, graphene, etc.). In order to grind the sodium ferric sulfate precursor to the required fineness (usually requiring D50 < 1 μm), a long grinding time (14-20 hours) and a high ball-to-material ratio (15:1-30:1) must be used. This leads to the following problems: (1) Low production efficiency: The single batch grinding cycle is long, and the output per unit time of the production line is extremely low, which cannot meet the needs of large-scale production; (2) Equipment is easily damaged: Long-term high-intensity grinding leads to severe wear of the equipment lining and grinding media, resulting in high equipment maintenance costs and a high failure rate; (3) Over-grinding and agglomeration: Over-grinding will produce a large number of new surfaces, and the surface energy will increase sharply, which will easily cause secondary agglomeration of particles, thereby reducing the dispersibility and electrochemical activity of the material. Disadvantages of single dry sand mill (or air jet mill, etc.) processes: Dry sand mills and air jet mills utilize high-speed airflow or high-speed rotating grinding discs to generate shearing force for fine grinding of materials. Their advantages lie in high grinding efficiency and narrow particle size distribution. However, when processing sodium ferric sulfate precursors, the initial mixture of ferrous sulfate monohydrate (or anhydrous ferrous sulfate), anhydrous sodium sulfate, and carbon sources (such as carbon nanotubes, conductive carbon black, graphene, etc.) is simply mixed before entering the equipment for grinding. Carbon has the characteristics of low specific gravity (about 0.1-0.3 g / cm³), large specific surface area, and high surface energy. The following problems are likely to occur in the grinding chamber: (1) Carbon source floating: In the high-speed rotating grinding chamber, the light carbon source is prone to float on the upper layer of the material or adhere to the inner wall and pipe of the equipment due to centrifugal force and airflow, and cannot effectively participate in grinding; (2) Uneven mixing: The carbon source cannot be uniformly mixed with the heavier iron and sodium source particles, resulting in uneven carbon distribution in the final material and incomplete conductive network; (3) Limited grinding efficiency: In order to improve the uniformity of mixing, it is necessary to increase the number of grinding cycles (such as 5-6 times). However, even so, the dispersion effect of carbon source is still not ideal, and the grinding time is greatly extended, losing the efficiency advantage of dry sand grinding.

[0011] In summary, how to balance grinding efficiency, equipment capacity, and carbon source dispersion uniformity in dry processes to achieve low-cost, high-efficiency, and high-performance large-scale production of sodium ferric sulfate cathode materials is a key technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0012] The main objective of this invention is to provide a sodium ferric sulfate cathode material and its graded dry grinding process to solve the problems of long grinding time, high ball-to-material ratio, equipment damage, and low production line output in existing single dry grinding processes, as well as carbon source floating, uneven mixing, and poor grinding effect in single dry sand mills. This invention employs a two-stage ball milling process of "coarse grinding with a vibratory ball mill (or horizontal mill) + fine grinding with a dry sand mill," achieving synergistic effects of "intense premixing and pre-coating" and "refined grinding and homogenization." This significantly improves production efficiency, reduces production costs, and extends equipment life while ensuring the electrochemical performance of the material.

[0013] To achieve the above objectives, the present invention provides the following technical solution: I. Raw material preparation and proportioning Weigh the iron source, sodium source, and carbon source according to the stoichiometric ratio of the target product.

[0014] Iron source: Selected from one or both of ferrous sulfate monohydrate (FeSO4·H2O) and anhydrous ferrous sulfate (FeSO4), with ferrous sulfate monohydrate being preferred (due to its more stable structure). The ferrous sulfate monohydrate or anhydrous ferrous sulfate can be obtained by directly purchasing finished products, or by using lower-cost ferrous sulfate heptahydrate (FeSO4·7H2O) as raw material, which is then dried and dehydrated. Drying equipment can include a rake vacuum dryer, a double cone vacuum dryer, a rotary kiln, etc., with a rake vacuum dryer being preferred. Using ferrous sulfate heptahydrate for self-drying can significantly reduce raw material procurement costs, and vacuum drying can effectively control the dehydration process, preventing ferrous ion oxidation and ensuring raw material purity.

[0015] Sodium source: selected from one or more of anhydrous sodium sulfate (Na2SO4), sodium carbonate (Na2CO3), and sodium hydroxide (NaOH). Anhydrous sodium sulfate is preferred to ensure consistency in the source of sulfur.

[0016] Carbon source: Selected from one or more of conductive carbon black (Super P), Ketjen black, acetylene black, carbon nanotubes (CNT), graphene, and carbon fiber. The amount of carbon source added is controlled between 1% and 5% of the total mass of the final product.

[0017] Target product: The general chemical formula of the final product is Na. 2+2X Fe 2-X (SO4)3, where 0 ≤ x ≤ 0.5, calculate the molar ratio of sodium, iron, and sulfur based on this chemical formula, and determine the raw material ratio accordingly. This is used to prepare Na. 2.5 Fe 1.75Taking (SO4)3 (i.e., x=0.25) as an example, the molar ratio of sodium, iron and sulfur elements calculated according to this chemical formula is Na:Fe:S = 2.5:1.75:3. Weigh the corresponding raw materials according to this ratio.

[0018] II. Primary Dry Coarse Milling (Premixing and Precoating) The weighed raw materials are directly added to a vibratory ball mill or a dry horizontal ball mill for primary dry coarse grinding.

[0019] Equipment Selection: Vibratory ball mills utilize the three-dimensional vibration generated by an eccentric shaft to cause the grinding media to produce high-frequency impact and grinding on the material, resulting in high mixing efficiency; dry horizontal ball mills use the rotation of the cylinder to drive the media to fall, generating impact and grinding effects, and have a simple structure and large processing capacity. Both types of equipment can achieve the coarse grinding purpose of this invention.

[0020] Grinding media: Zirconia balls or alumina balls. The media diameter is graded and mixed, preferably large balls (10-20 mm), medium balls (5-10 mm) and small balls (2-5 mm) in a mass ratio of (1-3):(1-3):(4-8) to balance impact crushing and grinding.

[0021] Ball-to-material ratio: 5:1 to 15:1 (mass ratio). Within this range, sufficient impact energy is provided while avoiding excessive media consumption and energy waste.

[0022] Grinding time: 2-6 hours. The goal at this stage is not to grind the material to its final fineness, but to achieve thorough mixing of the raw materials and pre-coating of the carbon source. Grinding time that is too short (<2 h) will result in insufficient mixing; grinding time that is too long (>6 h) will reduce efficiency and may lead to over-grinding.

[0023] Grinding atmosphere: The equipment cavity is filled with an inert atmosphere (such as nitrogen or argon) to prevent ferrous ions from being oxidized during the grinding process.

[0024] Third and second stage dry fine grinding (refinement and homogenization) The mixture obtained from the first coarse grinding is transferred to a dry sand mill for the second fine grinding.

[0025] Equipment Selection: Dry sand mill, which utilizes a high-speed rotating grinding disc to drive tiny grinding media, generating strong shearing and impact forces. It is suitable for fine grinding of submicron and even nanoscale materials. Specific process parameters are as follows: Grinding media: 0.1-2 mm zirconia beads. Smaller media size provides a higher shear frequency, which is beneficial for achieving material nano-sizing.

[0026] Grinding cycle count: 1-3 times. Each cycle refers to the material completing one full grinding process between the grinding chamber and the separation device.

[0027] Grinding atmosphere: Inert atmosphere (such as nitrogen or argon) protection.

[0028] IV. Sintering and Post-treatment The precursor powder, after two-stage dry grinding, is sintered and then further processed.

[0029] sintering: The precursor is sintered in a protective atmosphere furnace (such as a tube furnace, roller kiln, or rotary kiln). The sintering temperature is 350℃-400℃, and the holding time is 6-12 hours. During sintering, an inert gas (such as argon or nitrogen) or a reducing gas (such as an argon / hydrogen mixture) is used for protection. Protective atmosphere helps prevent the oxidation of ferrous ions.

[0030] Post-processing: Crushing and grading: The sintered material is crushed using an air jet mill or a mechanical mill, and then graded to obtain a finished product with uniform particle size distribution.

[0031] Demagnetization: An electromagnetic separator is used to remove magnetic impurities (such as iron filings) that may be introduced into the material, ensuring battery safety.

[0032] Packaging: Pack the processed finished materials into kilogram-level or ton-level packaging bags.

[0033] The innovations of this invention are reflected in the following aspects: (1) Functional division and coordination: The first-stage vibratory ball mill (or horizontal mill) utilizes the high impact force of large-sized grinding media to complete the initial crushing and mixing of raw materials in a short time. More importantly, through mechanochemical action, the lightweight carbon source is embedded and adhered to the surface of iron and sodium source particles under the impact force, realizing the "pre-coating" of the carbon source, which fundamentally solves the problem that the carbon source is difficult to mix with the main material due to its light weight. The second-stage dry sand mill utilizes the high shear force of small-sized media to finely grind the pre-coated composite particles, reducing the particle size to the submicron level, while further compacting and homogenizing the carbon coating layer to form a complete conductive network.

[0034] (2) Balance between efficiency and quality: By employing a two-stage division of labor, the extreme conditions that a single piece of equipment must endure to achieve the same effect are avoided. The vibratory mill only needs to perform "coarse grinding" rather than "fine grinding," thus significantly shortening the grinding time (2-6 hours), reducing the ball-to-material ratio (5:1-15:1), and significantly reducing equipment wear and energy consumption. The dry sand mill, because the carbon source has already been premixed in the feed, avoids the problem of carbon source floating, and only 1-3 cycles are needed to achieve the ideal nano-scale effect, greatly improving grinding efficiency. This invention adopts a two-stage grinding dry preparation process, which can significantly increase the output per unit time of the production line and effectively reduce the overall material cost. Attached Figure Description

[0035] Figure 1 A flowchart of the dry process for preparing sodium ferric sulfate cathode material by graded grinding.

[0036] Figure 2 This is a charge-discharge cycle diagram for Example 1.

[0037] Figure 3 This is a charge-discharge cycle diagram for Comparative Example 1.

[0038] Figure 4 The above is a charge-discharge cycle diagram for Comparative Example 2.

[0039] Figure 5 The above is a charge-discharge cycle diagram for Comparative Example 3.

[0040] Figure 6 The above is a charge-discharge cycle diagram for Comparative Example 4.

[0041] Figure 7 The above is a charge-discharge cycle diagram for Comparative Example 5.

[0042] Figure 8 The above is a charge-discharge cycle diagram for Comparative Example 6.

[0043] Figure 9 This is a charge-discharge cycle diagram for Example 2.

[0044] Figure 10 This is a charge-discharge cycle diagram for Example 3.

[0045] Figure 11 This is a charge-discharge cycle diagram for Example 4. Detailed Implementation

[0046] To make the technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention.

[0047] The flowchart of the graded grinding dry preparation process of sodium ferric sulfate cathode material in a specific embodiment of the present invention is as follows: Figure 1 As shown, the specific steps are detailed in the embodiment.

[0048] Example 1

[0049] This embodiment provides a method for preparing Na using "vibratory ball milling (coarse grinding) + dry sand milling (fine grinding)". 2.5 Fe 1.75 Specific methods for (SO4)3 cathode materials.

[0050] Step 1: Ingredients Taking a 10 kg ball-milled mixture (with a carbon content of approximately 3% of the sodium ferric sulfate cathode material) as an example, based on the chemical formula Na... 2.5 Fe 1.75 Based on the calculation of (SO4)3, the molar ratio of iron, sodium, and sulfur is 1.75:2.5:3. Approximately 6087.4 g of ferrous sulfate monohydrate (FeSO4·H2O, molecular weight 169.92), approximately 3632.1 g of anhydrous sodium sulfate (Na2SO4, molecular weight 142.04), and 280.5 g of carbon nanotubes (CNTs) were weighed.

[0051] Step 2: Primary coarse grinding (vibratory ball mill) The above raw materials were directly added to a 50 L vibratory ball mill. Zirconia balls were used as the grinding media, with large balls (12 mm in diameter), medium balls (8 mm in diameter), and small balls (4 mm in diameter) mixed in a mass ratio of 1:1:8, resulting in a total media mass to material mass ratio (ball-to-material ratio) of 8:1. Nitrogen gas was introduced into the mill jar for protection. The vibration frequency was set to 25 Hz, and the grinding time was 4 hours.

[0052] Step 3: Secondary fine grinding (dry sand grinding) The primary coarse abrasive is transferred to the feed hopper of the dry sand mill. The grinding media consists of 1 mm zirconia beads with a filling rate of 80%. Nitrogen gas is introduced into the chamber for protection during the grinding process. The grinding disc linear velocity is set to 12 m / s, and the material is circulated and ground twice (each cycle lasting approximately 30 minutes). The discharge temperature is controlled below 50℃.

[0053] Step 4: Sintering The precursor after secondary fine grinding was placed in a tube furnace under nitrogen atmosphere protection, heated to 370°C at a heating rate of 5°C / min, held for 8 hours and then cooled to room temperature.

[0054] Step 5: Post-processing The sintered material was pulverized using an airflow mill equipped with a closed-loop nitrogen system, and after classification, a finished powder with a D50 of 5-8 μm was obtained. Finally, magnetic impurities were removed using an electromagnetic demagnetizer to obtain the finished sodium ferric sulfate cathode material.

[0055] Comparative Example 1 (Single Vibration Ball Mill, Short Time) This comparative example uses a single vibratory ball milling process, with the same grinding time and ball-to-material ratio as the first-stage grinding time in Example 1, to compare the effects of two-stage grinding.

[0056] The ingredients for this comparative example are exactly the same as in Example 1. The materials are directly added to a vibratory ball mill, and the grinding media and their proportions are exactly the same as in Example 1. The ball-to-material ratio is 8:1, the grinding time is 4 hours, and the atmosphere is nitrogen protection. The ground materials are then directly sintered and post-treated, following the same process as in Example 1.

[0057] Comparative Example 2 (Single dry sand milling, short cycle) This comparative example uses a single dry sand milling process, with the same number of grinding cycles as in Example 1, to compare the effects of two-stage grinding.

[0058] The ingredients for this comparative example are exactly the same as in Example 1. The materials were simply mixed and then added to the feed hopper of a dry sand mill. The grinding media consisted of 1 mm zirconia beads, with a filling rate of 80%. Nitrogen gas was introduced into the chamber for protection during the grinding process. The grinding disc linear velocity was set to 12 m / s, and the material was circulated and ground twice (each cycle lasting approximately 30 minutes). The discharge temperature was controlled below 50°C. The ground material was then directly sintered and post-treated, following the same process as in Example 1.

[0059] Comparative Example 3 (Single horizontal ball mill, short time) This comparative example uses a single horizontal ball milling process to verify the performance of different equipment types under a single process.

[0060] The ingredients for this comparative example are exactly the same as in Example 1. The materials were directly added to a 50L horizontal ball mill. Zirconia balls were used as the grinding media, with large balls (15 mm in diameter), medium balls (10 mm in diameter), and small balls (5 mm in diameter) mixed in a mass ratio of 1:1:8 (ball-to-material ratio 12:1). The milling speed was 60 rpm, the grinding time was 6 hours, and the atmosphere was nitrogen protection. The ground materials were then directly sintered and post-treated, following the same process as in Example 1.

[0061] Comparative Example 4 (single vibratory ball mill, extended grinding time, increased ball-to-material ratio) This comparative example uses a single vibratory ball milling process, which improves the grinding effect by extending the grinding time and increasing the ball-to-material ratio, in order to compare the advantages of this invention in terms of production efficiency.

[0062] The ingredients for this comparative example are exactly the same as in Example 1. The materials are directly added to a vibratory ball mill, and the grinding media and their proportions are exactly the same as in Example 1. To improve the grinding effect, the ball-to-material ratio is increased to 15:1, the grinding time is extended to 14 hours, and the atmosphere is nitrogen protection. The ground materials are then directly sintered and post-treated, following the same process as in Example 1.

[0063] Comparative Example 5 (Single dry sand milling, with increased cycle count) This comparative example uses a single dry sand milling process, which increases the number of grinding cycles to improve the grinding and mixing effect, in order to compare the advantages of this invention in terms of production efficiency.

[0064] The ingredients for this comparative example are exactly the same as in Example 1. The materials are simply mixed and then added to a dry sand mill, with the number of grinding cycles increased to 6. All other parameters are the same as in Example 1. The ground material is then sintered and post-treated, following the same process as in Example 1.

[0065] Comparative Example 6 (single horizontal ball mill, extended grinding time, increased ball-to-material ratio) This comparative example uses a single horizontal ball milling process to verify the performance of different equipment types under a single process.

[0066] The ingredients for this comparative example are exactly the same as in Example 1. The materials were directly added to a 50L horizontal ball mill. Zirconia balls were used as the grinding media, with large balls (15 mm in diameter), medium balls (10 mm in diameter), and small balls (5 mm in diameter) mixed in a mass ratio of 1:1:8 (ball-to-material ratio 25:1). The milling speed was 60 rpm, the grinding time was 20 hours, and the atmosphere was argon protection. The ground materials were then sintered and post-treated, following the same process as in Example 1.

[0067] Example 2 (The primary coarse grinding equipment is replaced with a horizontal ball mill) The ingredients in this embodiment are the same as in Example 1. The material is directly added to a 50L horizontal ball mill. Zirconia balls are used as the grinding media, with large balls (15 mm in diameter), medium balls (10 mm in diameter), and small balls (5 mm in diameter) mixed in a mass ratio of 1:1:8 (ball-to-material ratio 12:1). The mill speed is 60 rpm, the grinding time is 6 hours, and the atmosphere is nitrogen protection. Subsequent secondary fine grinding, sintering, and post-treatment are exactly the same as in Example 1.

[0068] Example 3 (Adjustment of Secondary Fine Grinding Cycles and Media Size) The preparation steps in this embodiment are basically the same as those in Example 1, except that the grinding media of the dry sand mill is replaced with 0.5 mm zirconia beads, and the grinding is carried out once.

[0069] Example 4 (Iron source replaced with anhydrous ferric sulfate) The preparation steps in this embodiment are basically the same as in Example 1, except that ferrous sulfate monohydrate in the raw materials is replaced with anhydrous ferrous sulfate, according to the chemical formula Na... 2.5 Fe 1.75Based on the calculation of (SO4)3, the molar ratio of iron, sodium, and sulfur is 1.75:2.5:3. Weigh approximately 5817 g of anhydrous ferrous sulfate (FeSO4, molecular weight 151.91), approximately 3883 g of anhydrous sodium sulfate (Na2SO4, molecular weight 142.04), and 300 g of carbon nanotubes (CNTs), ensuring a total raw material weight of 10 kg.

[0070] Performance testing:

[0071] The sodium ferric sulfate cathode material prepared in the above examples and comparative examples was used as the cathode active material (80%), supplemented with Super P conductive carbon black (10%) and PVDF binder (10%) to form an electrode sheet. A sodium metal sheet was used as the counter electrode, and a glass fiber membrane was used as the separator. A CR2032 coin cell sodium-ion battery was assembled for testing, with a test voltage of 2.0V-4.5V. The electrolyte was a 1M NaClO4 EC / PC (1:1 v / v) solution with 5% FEC additive. All batteries were tested at 25℃, with the test cycle consisting of 5 cycles at 0.1C followed by a 0.5C cycle. The charge-discharge cycle diagram is shown below. Figure 2-11 As shown. Where Na 2.5 Fe 1.75 The theoretical specific capacity of (SO4)3 is 106 mAh / g.

[0072] Table 1: Electrochemical properties of sodium ferric sulfate NFS cathode material

[0073] Results analysis:

[0074] The data in Table 1 shows that: I. Performance Advantages: The sodium ferric sulfate cathode material prepared in Example 1 of this invention exhibits a significantly higher 0.1C specific capacity (94.53 mAh / g) than comparative examples 1, 2, and 3 (approximately 59-75 mAh / g) using a single device and with similar grinding times. It is also superior to comparative examples 4, 5, and 6 (approximately 80-85 mAh / g) where the grinding time or number of grinding cycles was significantly extended to pursue higher performance. This demonstrates that the two-stage grinding process has a synergistic effect on carbon source dispersion and particle nanostructuring.

[0075] II. Efficiency Advantages: While ensuring performance, the output per unit time of the process of this invention (Examples 1 and 2-4) is far higher than that of the long-term grinding process using a single device (Comparative Examples 4, 5, and 6). This indicates that the present invention significantly improves the production efficiency of the production line and effectively reduces the unit production cost.

[0076] III. Process Flexibility: The results of Examples 2-4 show that the core process (two-stage grinding) of the present invention has good versatility and can be applied to different types of primary grinding equipment, carbon sources, and iron sources. The efficiency can be further optimized by adjusting the secondary grinding parameters, and it has broad application prospects.

[0077] In summary, this invention innovatively proposes a two-stage dry grinding process of "violent ball mill (or horizontal mill) coarse grinding + dry sand mill fine grinding," which successfully solves the problems of low efficiency, uneven carbon source dispersion, and high equipment wear in the preparation of sodium ferric sulfate cathode materials by using a single dry grinding equipment. This enables the low-cost, high-efficiency, and large-scale preparation of high-performance sodium ferric sulfate cathode materials, and has significant technological progress and industrial application value.

[0078] Mechanism analysis:

[0079] The synergistic effect mechanism of the two-stage grinding dry preparation process described in this invention can be explained in detail from the following three aspects: (1) Mechanism of carbon source pre-coating under mechanochemical action In the primary coarse grinding stage, the grinding media in a vibratory ball mill (or horizontal mill) generate high-frequency impact and compression on the material, constantly creating fresh interfaces on the particle surface, with local instantaneous temperatures reaching hundreds of degrees Celsius. Under this mechanical force, lightweight carbon sources (such as carbon nanotubes and conductive carbon black) are forced into the surface of iron and sodium source particles or into the gaps between particles, forming an "anchoring" effect. Simultaneously, the mechanical force causes micro-regional softening or plastic deformation of the iron source (ferrous sulfate monohydrate) particle surface, which is beneficial for the adhesion and fixation of the carbon source. This pre-coated structure provides the foundation for the subsequent secondary fine grinding: the carbon source no longer exists in a free, lightweight state but is firmly attached to the surface of the main material particles, fundamentally solving the problem of carbon source flotation in dry sand milling.

[0080] (2) Particle size evolution and interfacial bonding enhancement mechanism Two-stage grinding achieves a stepwise evolution of particle size. The first stage, coarse grinding, breaks down the original particles (D50 approximately 50-200 μm) to 10-30 μm. This stage mainly relies on impact force to achieve macroscopic particle breakage and mixing. The second stage, fine grinding, uses small-sized grinding media (0.5-2 mm) to finely grind the pre-coated composite particles in a shear force field generated by high-speed rotation. The main functions of this stage include: ① further breaking down the particles to the submicron level (D50 ≤ 1 μm), significantly shortening the diffusion path of sodium ions in the solid phase; ② through high-frequency shearing, mechanical fusion occurs at the interface between the carbon source and the active particles, forming a tight "core-shell" structure and enhancing the adhesion of the carbon coating layer; ③ the high-frequency collision of the small-sized media ensures that the carbon source is evenly spread on the surface of the active particles, avoiding local carbon agglomeration or exposure.

[0081] (3) Mechanism of conductive network construction and electrochemical performance enhancement During sintering, the uniform carbon coating layer formed after secondary fine grinding constructs a three-dimensional conductive network in situ on the surface of the active particles. Because the carbon source achieves close contact and uniform distribution with the active particles during the grinding stage, the conductive network formed after sintering is more continuous and complete. This structure has the following electrochemical advantages: ① The carbon network provides a fast electron transport channel, reducing electrode polarization; ② The uniform coating layer effectively buffers volume changes during charge and discharge, suppressing particle pulverization and interfacial side reactions; ③ The synergistic effect of submicron-sized particles and the uniform carbon network improves the utilization rate of the active material, achieving a specific capacity of 90-95 mAh / g and significantly enhancing cycle stability.

[0082] In summary, this invention achieves multi-scale structural control through a two-stage grinding process, encompassing "macroscopic mixing → microscopic coating → nano-sizing and network construction," which is impossible to achieve with a single-equipment dry process.

[0083] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A graded grinding dry preparation process for sodium ferric sulfate cathode material, characterized in that, Includes the following steps: (1) First-stage dry coarse grinding: Iron source, sodium source and carbon source are mixed in proportion and added to a vibrating ball mill or a horizontal ball mill for first-stage dry coarse grinding to obtain a pre-coated precursor; (2) Secondary dry fine grinding: The pre-coated precursor obtained in step (1) is transferred to a dry sand mill for secondary dry fine grinding to obtain a nano-sized precursor; (3) Sintering: The nano-precursor obtained in step (2) is sintered in an inert atmosphere or a reducing atmosphere to obtain the sintered product; (4) Post-processing: The sintered product obtained in step (3) is crushed, classified and demagnetized to obtain sodium iron sulfate cathode material.

2. The preparation process according to claim 1, characterized in that, The iron source in step (1) is selected from one or two of ferrous sulfate monohydrate (FeSO4·H2O) and anhydrous ferrous sulfate (FeSO4); the sodium source is selected from one or more of anhydrous sodium sulfate (Na2SO4), sodium carbonate (Na2CO3), and sodium hydroxide (NaOH); the carbon source is selected from one or more of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, graphene, and carbon fiber; the amount of carbon source added is 1%-5% of the total mass of the final product.

3. The preparation process according to claim 1, characterized in that, The process parameters for the first-stage dry coarse grinding in step (1) are: ball-to-material mass ratio of 5:1-15:1, grinding time of 2-6 hours, grinding media of zirconia balls or alumina balls, and grinding under an inert atmosphere.

4. The preparation process according to claim 3, characterized in that, The grinding media are graded and proportioned, with large balls (10-20 mm), medium balls (5-10 mm), and small balls (2-5 mm) mixed in a mass ratio of (1-3):(1-3):(4-8).

5. The preparation process according to claim 1, characterized in that, The process parameters for the secondary dry fine grinding in step (2) are as follows: the grinding media is 0.1-2 mm zirconia beads, the grinding cycle is 1-3 times, and the grinding is carried out under an inert atmosphere.

6. The preparation process according to claim 1, characterized in that, The sintering temperature in step (3) is 350℃-400℃, the holding time is 6-12 hours, and the sintering atmosphere is argon, nitrogen or argon / hydrogen mixture.

7. The preparation process according to claim 1, characterized in that, The iron source mentioned in step (1) is preferably ferrous sulfate heptahydrate (FeSO4·7H2O) obtained by drying and dehydration. The drying equipment is selected from rake vacuum dryer, double cone vacuum dryer or rotary kiln.

8. The preparation process according to claim 1, characterized in that, The general chemical formula of the sodium ferric sulfate cathode material is Na. 2+2X Fe 2-X (SO4)3, where 0≤x≤0.5, calculate the molar ratio of sodium, iron and sulfur based on this chemical formula, and determine the proportion of raw materials accordingly.

9. A sodium ferric sulfate cathode material, characterized in that, It is prepared using the preparation process described in any one of claims 1-8.

10. The sodium ferric sulfate cathode material according to claim 9, characterized in that, The material has a 0.1C specific capacity of 90-95 mAh / g and a first-cycle coulombic efficiency of ≥90%.